2015
DOI: 10.1017/s0022377815000185
|View full text |Cite
|
Sign up to set email alerts
|

Multipoint observations of plasma phenomena made in space by Cluster

Abstract: Plasmas are ubiquitous in nature, surround our local geospace environment, and permeate the universe. Plasma phenomena in space give rise to energetic particles, the aurora, solar flares and coronal mass ejections, as well as many energetic phenomena in interstellar space. Although plasmas can be studied in laboratory settings, it is often difficult, if not impossible, to replicate the conditions (density, temperature, magnetic and electric fields, etc.) of space. Single-point space missions too numerous to li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 381 publications
(571 reference statements)
0
15
0
Order By: Relevance
“…The standard method for describing the parts of the magnetic power spectrum is via an energy‐cascade picture. Sketches of the cascade concept of the solar wind magnetic spectrum can be found in Figure 19 of Goldstein et al (), Figure 2 of Howes (), and Figure 14of Matthaeus et al (). The first column of Figure lists the main concepts used in that method of describing the solar wind's magnetic power spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…The standard method for describing the parts of the magnetic power spectrum is via an energy‐cascade picture. Sketches of the cascade concept of the solar wind magnetic spectrum can be found in Figure 19 of Goldstein et al (), Figure 2 of Howes (), and Figure 14of Matthaeus et al (). The first column of Figure lists the main concepts used in that method of describing the solar wind's magnetic power spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic scales at which this break-down occurs are given by the proton gyro-radius ρ p = v th,p /Ω p (being v th,p the proton thermal speed and Ω p the proton gyrofrequency) and/or the proton skin depth d p = c/ω cp (being c the speed of light and ω cp the proton plasma frequency) [2,[4][5][6]. At these scales the dynamics could be mediated by kinetic-Alfvén fluctuations, whistler-like perturbations and coherent structures such as vortexes and current sheets [7].The most narrow current sheets and filaments are present at electron scales, where turbulent energy eventually dissipates [8,9], even if the energy-dissipation mechanisms in a weakly-collisional plasma such as the turbulent solar wind are far from being understood. Recent kinetic simulations…”
mentioning
confidence: 99%
“…The most narrow current sheets and filaments are present at electron scales, where turbulent energy eventually dissipates [8,9], even if the energy-dissipation mechanisms in a weakly-collisional plasma such as the turbulent solar wind are far from being understood. Recent kinetic simulations…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The spin‐integrated differential particle flux in cm −2 s −1 sr −1 keV −1 as a function of time is shown in Figure a. Density ( n ) and heat flux parallel to the magnetic field ( H || ) were calculated using a trapezoidal integration scheme that was validated against existing Cluster moments code [ Goldstein et al , ] and are shown in Figures b and c, respectively. From reported N(v) and f ( v ) values, the covariance matrix was calculated following section 2.…”
Section: Uncertainties From Cluster/peacementioning
confidence: 99%